Beef caule toeding ciltical periods on native pastures in the Brazilian ’Pantanal - Pott, Edison B.; Catto, João B.; Brum, Paulo A. R. de (Pesquisa Agropecuaria Brasileira, 2014)
The weight development of 20 male and 20 female calves tom one to three months until 32 to 34 months of age, from October 1977 to May 19801 in the Nhecolândia subregion, and of 89 heifers, from weaning to first conception, from February 1980 to September 1983, in the Paiaguás subregion, was monitored, with the objective of identifying the critical feeding periods for the beef cattle herd. Two periods of feeding restriction were observed, one from the peak to the end of flooding (February lo May) and the other from the middle lo the end of the dry season (August to September). The differences between the two subregions and the effect of the wet/dry cycles on the growth curves and on calving rates are discussed.